Modulação da memória de medo sob diferentes aspectos : um estudo dinâmico envolvendo a neurotrasmissão serotoninérgica, as enzimas anidrases carbônicas e o estresse do tipo social - Schmidt, Scheila Daiane (2018)
Conditioned fear is an important form of learning and memory, being essential for the adaptation, maintenance and survival of animal species. Different neural substrates and brain areas are required in the consolidation, reconsolidation and extinction processes of fear memory. The aim of the present study was to verify (i) the role of 5-HT5A, 5-HT6 and 5-HT7 serotonin receptors on the stabilization processes of contextual fear conditioning (CFC) memory, (ii) the involvement of the carbonic anhydrases enzymes (CAs) on the extinction of CFC memory and (iii) the effects of social instability stress on the consolidation of CFC memory. For this, male Wistar rats were submitted to CFC task. It has been found that, in the CA1 region of the dorsal hippocampus, 5-HT5A receptor blockade and 5-HT6 receptor activation do not interfere on the consolidation, but impairs the reconsolidation of CFC memory. It was further observed that 5-HT6 receptor blockade of the CA1 region impairs the consolidation, but does not interfere on the reconsolidation of CFC memory. Interestingly, blockade of the 5-HT7 receptor of the CA1 region modulates the consolidation and reconsolidation of the CFC memory, facilitating both processes. It has also been found that the inhibition of CAs does not impair the acquisition, but rather the consolidation of the CFC extinction memory. This damage occurred through a central mechanism of action in which the CA1 regions of the hippocampus, basolateral amygdala and ventromedial prefrontal cortex (vmPFC) are involved. Animals that demonstrated impairment in the consolidation of CFC extinction memory after inhibition of CAs in vmPFC, showed an increase in c-Fos expression in this region. Finally, it was observed that social instability stress in adolescence impairs the consolidation of CFC memory, an effect that persists in adulthood. A diet rich in Vitamin A and omega 3 was able to prevent this effect at both stages of life. Animals stressed with the control diet had a reduction in the expression of hippocampal BDNF in adolescence and adulthood, which was also prevented in both periods by consumption of the enriched diet. The results obtained in this work make it possible to broaden the understanding of the molecular mechanisms underlying the processes of consolidation, reconsolidation and extinction of MCC memory, serving as a basis for future researches that seek the treatment of clinical conditions in which fear memory processing is altered.